Answer:
Perimeter square = 8 sqrt(pi)
Step-by-step explanation:
The perimeter of a square is 4*s
The area of a circle is Area = pi * r^2
The circumference of a circle is C = 2*pi * r
C = 4 pi
4pi = 2*pi * r
r = 2
So the area of the circle is pi * r^2 = pi * 2^2 = 4pi
The square has the same area
Area = 4*pi
Square = 4*pi
s^2 = 4*pi
s = sqrt(4*pi)
s = 2*sqrt(pi)
The perimeter = 4 * 2 * sqrt(pi)
The perimeter = 8 * sqrt(pi)
The mass in kg is 106.27 if the mass of a cube, M (kg), is proportional to the cube of the length of its edge, L(m).
<h3>What is a proportional relationship?</h3>
It is defined as the relationship between two variables when the first variable increases, the second variable also increases according to the constant factor.
We have:
The mass of a cube, M (kg), is proportional to the cube of the length of its edge, L(m).
M ∝ L³
After removing proportional sign
M = cL³
Plug M = 50 kg and L = 70 cm = 0.7 m
50 = c(0.7)³
c = 145.77 kg/m³
If L = 0.9 m, then M
M = (145.77 kg/m³)(0.9 m)³
M = 106.266 ≈ 106.27 kg
Thus, the mass in kg is 106.27 if the mass of a cube, M (kg), is proportional to the cube of the length of its edge, L(m).
Learn more about the proportional here:
brainly.com/question/14263719
#SPJ1
Step-by-step explanation:
<u>This number given in the above question is the square root of 3/10</u> .
First of all ,
we can write 9 as 3²,
and 100 can be written as 10².
⇒ Now when we take the root of this two -
⇒ √ 3²/10²
we get ,
⇒ 3/10
The square root of 9/100 is <u>3/10</u> .
Answer:
David receives £90
Step-by-step explanation:
Let David's share be D
Let Mark's share be M
Let Henry's share be H
From the question, we obtained the following data:
David gets twice as much as Mark i.e
D = 2M
M = D/2
Mark gets three times as much as Henry i.e
M = 3H
H = M/3
H = (D/2) /3
H = D/6
The sum of their shares is £150 i.e
D + M + H = 150
D + D/2 + D/6 = 150
Multiply through by 6 to clear the fraction
6D + 3D + D = 900
10D = 900
Divide both side by the coefficient of D i.e 10
D = 900/10
D = 90
Therefore, David receives £90
Answer:
[2x-4]<x-1 so we take off the brackets so
2x-4<x-1
group like terms so
2x-x<-1+4
x < 3